Subbarrier fusion of carbon isotopes: from resonance structure to fusion oscillations. (March 2015) - Hagino, K; Rowley, N
Abstract: At energies below the Coulomb barrier, the fusion excitation function for the 12 C+ 12 C system shows prominent fine structures, whereas that for the 12 C+ 13 C system behaves more smoothly as a function of energy. We demonstrate that these different behaviors can be simultaneously reproduced using an optical potential in which the strength of the imaginary part is proportional to the level density of each compound nucleus. We also discuss the oscillatory behavior of fusion excitation function for these systems observed at energies above the Coulomb barrier from a view point of quantum mechanical systems with identical particles.